HUBUNGAN ANTARA EFEKTIVITAS KOMUNIKASI INTERPERSONAL SISWA DAN GURU DENGAN PROKRASTINASI AKADEMIK PADA SISWA SMA NEGERI “X” - Karina Aria Putri; Dian Ratna Sawitri (Jurnal EMPATI, 2018)
Academic procrastination is a phenomenon that many students do in school. Lack of the effective communication between student and teacher can be one of the reasons who increase the academic procrastination on students. The aim of this research is to determine the relationship between the effective of interpersonal communication student and teacher with academic procrastination on the student. Population in this research is a student in XI and XII class with 678 students. This research using 233 sample obtained by cluster random sampling technique. Data retrieved by using two scales of effective interpersonal communication with 35 items (α= 0,916) and academic procrastination scale with 41 items (α= 0,908). The result of simple regression analysis showed there is a significant negative relationship between effective interpersonal communication with academic procrastination rxy= -0,490 (p<0,001). Which mean the higher effective interpersonal communication between students and teacher, getting lower academic procrastination on students. The effective of interpersonal communication contributed 24% to academic procrastination and 76% determined by other factor which is not discussed in this research.